2020
DOI: 10.1371/journal.pone.0231460
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors for post-traumatic stress among New Zealand military personnel: A cross sectional study

Abstract: Background Post-traumatic stress (PTS) is prevalent among military personnel. Knowledge of the risk and protective factors associated with PTS in this population may assist with identifying personnel who would benefit from increased or targeted support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 65 publications
0
28
0
Order By: Relevance
“…The survey questionnaire comprised of 80 questions in total and was based on five sections: the PTSD Checklist DSM-5 (which measures distress), the Acceptance and Action Questionnaire (AAQ-2), Audit-C Assessment Tool, the Brief Trauma Questionnaire, and the Sleep Condition Indicator. In summary, the questionnaire included a number of standardised measures of post-traumatic stress (outcome) and six exposure variables (Richardson et al , 2020). The survey also included questions pertaining as to whether the respondent worked at a 1, 2 or 3 person station, they were a member of a specialist group and whether they had been shot at.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The survey questionnaire comprised of 80 questions in total and was based on five sections: the PTSD Checklist DSM-5 (which measures distress), the Acceptance and Action Questionnaire (AAQ-2), Audit-C Assessment Tool, the Brief Trauma Questionnaire, and the Sleep Condition Indicator. In summary, the questionnaire included a number of standardised measures of post-traumatic stress (outcome) and six exposure variables (Richardson et al , 2020). The survey also included questions pertaining as to whether the respondent worked at a 1, 2 or 3 person station, they were a member of a specialist group and whether they had been shot at.…”
Section: Methodsmentioning
confidence: 99%
“…The odds ratio was used to measure the association between the exposure to the PSTD factor and its outcome or the possibility that it will occur (Schmidt and Kohlmann, 2008). As Richardson et al (2020) identified, the design of this survey framework enabled the potential exposures of trauma, general distress and hazardous drinking and the protective exposures of social support, sleep and psychological flexibility to be examined.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported factors associated with post-traumatic stress in this group, [26] using No other studies appear to have used the EQ-VAS as an outcome measure for Veteran health.…”
Section: Comparison With Other Studiesmentioning
confidence: 97%